Drain to the last drop - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The rainwater harvesting CD By H Hartung, co-publication Margraf CTA FAKT NEDA, 2002. ISBN 3 8236 1384 7 CTA number 1092. 40 credit points